Bearing Tribology Principles and Applications - Qiu, Ming.; Chen, Long.; Li, Yingchun; Yan, Jiafei; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2017)
By focusing on the theory and techniques of tribological design and testing for bearings, this book systematically reviews the latest advances in applications for this field. It describes advanced tribological design, theory and methods, and provides practical technical references for investments in bearing design and manufacturing. The theories, methods and cases in this book are largely derived from the practical engineering experience gained and research conducted by the author and her team since the 2000s. The book includes academic papers, technical reports and patent literature, and offers a valuable guide for engineers involved in bearing design. <The book is intended for engineers, researchers and graduate students in the field of mechanical engineering, especially in bearing engineering.
Friction, wear and lubrication in the bearing application -- Bearing surface contact -- Mechanism of bearing friction and wear -- Materials for bearing frictional pairs -- Sliding bearing lubrication theory -- Rolling bearing lubrication theory -- Bearing lubrication application -- Friction and wear testing technology in the bearing -- Fault diagnosis and status monitoring of the bearing -- Applied tribology in the bearing.
Keywords: Machinery; Coatings; Tribology; Corrosion and anti-corrosives.; Engineering design; Machinery and Machine Elements; Coatings; Tribology; Corrosion; Engineering Design